2008
DOI: 10.1038/sj.bjc.6604618
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycaemic index, glycaemic load and breast cancer risk: a systematic review and meta-analysis

Abstract: This systematic review aimed to examine if an association exists between dietary glycaemic index (GI) and glycaemic load (GL) intake and breast cancer risk. A systematic search was conducted in Medline and Embase and identified 14 relevant studies up to May 2008. Adjusted relative risk estimates comparing breast cancer risk for the highest versus the lowest category of GI/GL intake were extracted from relevant studies and combined in meta-analyses using a random-effects model. Combined estimates from six cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
(62 reference statements)
2
32
1
1
Order By: Relevance
“…Some systematic reviews and revisions (Esfahani et al, 2009;Gnagnarella et al, 2008;Mente et al, 2009) demonstrate the value of using these indicators, but others do not show this relevance (Dong & Qin, 2011;Mulholland et al, 2008Mulholland et al, , 2009. There is still a long way to go for researchers regarding this issue to ensure that GI and GL are quantified and addressed in studies on consumption and dietary prescription aimed at promoting health and preventing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some systematic reviews and revisions (Esfahani et al, 2009;Gnagnarella et al, 2008;Mente et al, 2009) demonstrate the value of using these indicators, but others do not show this relevance (Dong & Qin, 2011;Mulholland et al, 2008Mulholland et al, , 2009. There is still a long way to go for researchers regarding this issue to ensure that GI and GL are quantified and addressed in studies on consumption and dietary prescription aimed at promoting health and preventing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that only the GL had a positive association with breast cancer risk (Gnagnarella et al, 2008). Another metabased on menopausal status because the heterogeneity, was observed in both premenopausal and postmenopausal women (Mulholland et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Few studies have assessed the associations stratified by hormone receptor status, [12][13][14] although breast cancers classified by estrogen receptor (ER) and progesterone receptor (PR) expression likely have different etiology. 15 We examined the associations of carbohydrate intake, glycemic index and glycemic load with the incidence of breast cancer, overall and stratified by ER and PR status of the tumor, in a population-based prospective cohort of Swedish women.…”
Section: Uiccmentioning
confidence: 99%